Constitutional foundings in Northeast Asia - Ng, Michael; Tan, Kevin, YL (London [England] : Hart Publishing, 2021)
"This new book in the Constitutionalism in Asia series considers the idea of origins, and of change and continuity in terms of 'constitution-making', which is an on-going process in the Northeast Asian states. The book examines the drafting, nature, core values and roles of the first modern constitutions during the founding of the eight modern states/territories in Northeast Asia: China (1949) Taiwan (1947) Hong Kong SAR (1997) Macau (1993) Japan (1889) North Korea (1948 or 1972) South Korea (1948) Mongolia (1992) The collection provides: - an exploratory description of the process and substantive inputs in the making of the first constitutions of these nations; - analysis of the internal and external (including intra-regional) forces surrounding the making of these constitutions; and - theoretical construction of models to conceptualise the nature and role of the first constitutions (including constituent documents) in the founding of the modern nation-states and their subsequent impact on state-building in the region."--
1. Constitutional Foundations in Northeast Asia: A Reflective Introduction / Kevin YL Tan -- 2. The 1954 Constitution of China: Empire State-Building / Humphrey Ko -- 3. The Birth of the Constitution of the Republic of China / Chien-Chih Lin -- 4. Sino-British Diplomacy in the Making of the Constitutional Order of Hong Kong: Historical Investigations into the Drafting of the Joint Declaration and Basic Law (1982-1990) / Albert HY Chen and Michael Ng -- 5. Macau's Constitutional Founding / Xiaobo Zhai -- 6. Constitutional Founding of the Democratic People's Republic of Korea / Erik Mobrand -- 7. Thirty Years Old at Birth? The Constitutional Founding of the Republic of Korea / Chaihark Hahm -- 8. The Meiji Constitution and Japan's Emergence in the International Order, 1853-1905 Kentaro Matsubara -- 9. The Role and Importance of the First Constitution of Mongolia / Batbold Amarsanaa, Masaki Nakamura and Chandraabal Unurbayar.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Constitutional law -- East Asia; Constitutional & administrative law; East Asia -- Politics and government; Electronic books